"A lot of head wraps": African contributions to the third wave of electoral gender quotas. (2nd April 2016) - Bauer, Gretchen
Abstract : Over the last more than two decades, political parties and governments across sub-Saharan Africa (SSA) have adopted electoral gender quotas for parliament at an astonishing rate – and with remarkable success as many sub-Saharan African countries have catapulted to the top in terms of women's representation in a single or lower house of parliament. During a first wave in East and Southern Africa (part of a global "second wave"), quotas were adopted in the aftermath of conflicts and in the course of political transitions as mobilized national women's movements, influenced by an international women's movement and international norms, took advantage of political openings to press for the adoption of quotas through new constitutions or new electoral laws. In some cases a clear diffusion effect was at play between political movements that closely influenced one another and across national borders. During a second wave mostly, though not only, in West Africa (part of a global "third" wave), quotas are again being adopted as women's movements, in collaboration with regional, continental, and international organizations, similarly press for an increased representation of women during constitutional reform processes or through revisions to electoral laws. During this second wave in SSA, women activists and governments have sought to strengthen existing electoral gender quotas or adopt them for the first time – going as far as seeking gender parity in a handful of cases. In most ways, SSA conforms to international trends in second and third wave quota adoption, though not without some regional variation. This article explores some of the ways in which the sub-Saharan African experience has been distinctive – focusing on the adoption of parity quotas in Senegal, Tanzania, and Zimbabwe – and some of the remaining challenges affecting the adoption and implementation of electoral gender quotas across the continent.